ISO, Contract Management And Blockchain On Profit Quality - Tjun, Lauw Tjun; Sabrina, Olivia Windy; Thoma, Caritas Ignasia Yeni (Universitas Dharma Wacana, 2023)
The purpose of this research is to determine the effect of ISO, Management Contracts, and Blockchain on Earnings Quality in manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The 2016-2018 period was chosen because before the COVID-19 pandemic, Inondesia's economic condition was still stable, thus providing ideal information to see the company's performance. The approach of this research is quantitative research. The population of this research is 10 companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique is done by using purposive sampling method that produces 30 samples during 2016-2018. The data used are secondary data taken through documentation techniques consisting of manufacturing companies annual report in 2016-2018. The method of data analysis in this research is panel data regression analysis. The results showed that Blockchain has a positive influence on Earnings Quality, ISO and Contract Management have no influence on Earnings Quality